2017
DOI: 10.51200/ljms.v11i.722
|View full text |Cite
|
Sign up to set email alerts
|

The Scenario of Giving to Beggars: A Behavioural Analysis Among Malaysians

Salwa Amirah Awang,
Joni Tamkin Borhan,
Mohamad Taqiudin Mohamad
et al.

Abstract: Giving to beggars has become a national issue as it gives negative impact to the society especiallyrelated to the image of the country and social health. Despite the fact that many attempts havebeen taken by the authority to curb this problem, the population of beggars are seen to begrowing. Thus, this study aims to analyse the behaviour of giving among Malaysians to find thecauses of the problem and ways to overcome this issue by employing an extended version of TheTheory of Planned Behaviour. Intrinsic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Verhaert and Van de Poel (2001) studied 1,385 respondents in the United Kingdom and discovered that subjective norms significantly influence donor behaviour to European charity. Awang et al (2017) examined 1034 respondents in three Malaysian states and confirmed that subjective norms influenced the behaviour of giving to beggars. Subsequently, a study by Muhammad et al (2014b) involving 101 Muslim teachers in Johor, Malaysia, revealed that family members are involved in influencing the contribution of alumni to the university.…”
Section: Subjective Normsmentioning
confidence: 86%
“…Verhaert and Van de Poel (2001) studied 1,385 respondents in the United Kingdom and discovered that subjective norms significantly influence donor behaviour to European charity. Awang et al (2017) examined 1034 respondents in three Malaysian states and confirmed that subjective norms influenced the behaviour of giving to beggars. Subsequently, a study by Muhammad et al (2014b) involving 101 Muslim teachers in Johor, Malaysia, revealed that family members are involved in influencing the contribution of alumni to the university.…”
Section: Subjective Normsmentioning
confidence: 86%
“…The conceptual framework in the study of the Analysis of the Causes and Impacts of the Existence of Homeless and Beggars in the City of Medan is as follows (Awang et al, 2017)…”
Section: Conceptual Frameworkmentioning
confidence: 99%